LOCAL GOVERNMENT: EXAMINING FACTORS AFFECTING AUDIT REPORT LAG - Sianturi, Antar MT; Siahaan, Magda (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
Audit report lag, especially in local governments, needs to be studied in depth regarding the causes of its occurrence. The purpose of this study is to examine the direct influence of opinion, audit findings, educational background, professional skills, and continuing professional education on audit report lag in local governments. The population of the study was the audit report of local governments, with a purposive sampling technique of 535 local governments' Financial Reports from a total population of 539 local governments or 99.26%. After being analyzed using SPPS, the results of this study showed that opinion, educational background, and continuing professional education had a positive effect. In contrast, audit findings and professional skills did not significantly affect audit reporting delays.